2017
DOI: 10.1111/gove.12330
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerating good governance: Regime type and score inflation among executive survey informants

Abstract: Researchers and policymakers often rely on executive surveys to understand and promote good governance. In doing so, they assume that the evaluations provided by these well‐informed respondents are not systematically influenced by regime type. However, regime‐embedded executives often have a personal stake in the survey outcomes, incentivizing them to exaggerate good governance. This paper compares World Economic Forum Executive Opinion Survey responses to corollary measures of key governance concepts in democ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Widening the scope of our studies to include developing countries also substantially increases the number of units whose behavior we can observe, as recent work published in Governance demonstrates (cf. Jindra & Vaz, 2019; Shockley, Ewers, Nardis, & Gengler, 2018; Stockemer & Sundstrom, 2019). The role of international organizations, or, for instance, country performance rankings (see e.g., Kelley & Simmons, 2020) can be better understood, and influences better identified, through an increase in statistical power that is borne of the widening of our cross‐country scope.…”
Section: To Understand Domestic Public Administration Look Beyond Itmentioning
confidence: 99%
“…Widening the scope of our studies to include developing countries also substantially increases the number of units whose behavior we can observe, as recent work published in Governance demonstrates (cf. Jindra & Vaz, 2019; Shockley, Ewers, Nardis, & Gengler, 2018; Stockemer & Sundstrom, 2019). The role of international organizations, or, for instance, country performance rankings (see e.g., Kelley & Simmons, 2020) can be better understood, and influences better identified, through an increase in statistical power that is borne of the widening of our cross‐country scope.…”
Section: To Understand Domestic Public Administration Look Beyond Itmentioning
confidence: 99%
“…The closed political environment also restricts the availability and accuracy of secondary data on governance commonly collected and publicised by external organisations such as the World Bank, World Economic Forum and others. Quantitative studies have demonstrated systematic bias in such data caused by the political embeddedness of the elite survey informants on whose judgements these surveys rely (Shockley et al, 2018). Indeed, in August 2020 the World Bank publicly suspended its high-profile annual Doing Business report after discovering 'data irregularities' that artificially boosted the ratings of at least four autocratic countries (Zumbrun, 2020).…”
Section: Gauging Governance In the Face Of The Pandemicmentioning
confidence: 99%